Natalka Gold Deposit - Nikitenko E.M.; Mikhalitsyna T.I.; Fomina V.I.; Sotskaya O.T. (My University, 2014)
Studies were taken of ore-bearing rocks, ores and gravity concentrates from Natalka gold deposit by a set of complex methods including mineralogical, petrographic and geochemical research, gravity concentration, and electronic microscopy. The major form of Au found is native: free gold is larger and dispersed, in the form of microinclusions. The obtained results are the basis for an effective technology to extract gold and sequence of profitable mining of Natalka deposit.
Keywords: Yana-Kolyma Fold System; Natalka Gold Deposit; Mineralogical and Petrographic Characteristics; Chemical Composition; Gravitational Concentrates